Autonomous Pronunciation Learning in Higher Education Via Heutagogical Strategies: Implementation, Challenges, and Solutions - Yulianto Sabat; Abd. Syakur; Lailatul Musyarofa; Ika Rahmania (JTP - Jurnal Teknologi Pendidikan, 2026)
heutagogical strategies. While many studies have explored heutagogy across disciplines, limited research has addressed its application in pronunciation learning. This study examines how heutagogical principles are implemented in pronunciation instruction, highlighting the importance of pronunciation in effective oral communication. This study adopts a qualitative case study design involving two pronunciation lecturers at a higher education institution. Data were collected through classroom observations and semi-structured interviews. The study addressed three questions: (1) How is heutagogy applied in pronunciation learning? (2) What challenges are encountered by lecturers? (3) What strategies are used to overcome these challenges? The findings reveal that lecturers promoted learner autonomy through self-directed tasks, flexible learning pathways, and the integration of digital tools. Pronunciation websites and mobile applications were widely used to support independent practice and provide immediate feedback. However, challenges included students’ limited self-regulation, unequal access to digital devices, and lecturers’ varying technological skills. To address these challenges, lecturers engaged in professional development activities such as webinars and discussions. Students were supported through device sharing and campus internet facilities. These findings suggest that heutagogy has strong potential for pronunciation learning, but requires adequate institutional support and digital readiness in practice. This study contributes to the development of learner-centered approaches by emphasizing the role of autonomy and technology in language learning contexts, particularly in higher education settings where digital resources and independent learning are increasingly essential for improving students’ pronunciation competence and overall communicative performance in diverse educational contexts worldwide.